Design of Sentiment Analysis on Indodax Instagram Social Media Comments About Cryptocurrency Using Naïve Bayes Classifier - Dimas Prayoga (Al'Adzkiya, 2024)
In today's digital era, social media such as Instagram has become the main platform for many individuals to interact and express opinions online. One application that is often the subject of conversation is Indodax, a well-known digital asset trading platform in Indonesia. This research aims to evaluate the sentiment of Instagram users towards Indodax services through a sentiment analysis approach using Naive Bayes Classifier. The data collected consists of Instagram users' comments, which are analyzed to assess the tendency of their sentiments, whether positive or negative towards Indodax services. This method applies probability and statistical concepts to classify sentiments based on the words present in the comments. It is hoped that the results of this study can provide insights for Indodax to improve the quality of their services based on the perceptions of users. Based on the experiments conducted, the Naive Bayes Classifier method shows fairly accurate classification results, so it can support sentiment analysis related to the Indodax application.